2008
DOI: 10.1017/s0376892908005213
|View full text |Cite
|
Sign up to set email alerts
|

Are citizens' juries a useful tool for assessing environmental value?

Abstract: Stated preference valuation surveys, such as choice modelling, are the preferred choice for environmental valuation of water quality improvements. Such willingness to pay (WTP) surveys commonly rely on face-to-face interviews or mail-out questionnaires on a relatively large representative sample of the target population. There is increasing concern that survey respondents may have insufficient information and limited opportunity to deliberate prior to stating their preferences about their WTP. Citizens' juries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 28 publications
(74 reference statements)
0
20
0
Order By: Relevance
“…Previous work highlights that group-based approaches are more appropriate when dealing with unfamiliar and complex questions given that a group setting facilitates information sharing and deliberation (Robinson et al, 2008;Lienhoop & Fischer, 2009). Further, collective decision making is of great interest when it comes to participatory planning, given that relevant decisions will be made in the context of small unitary groups (Kocher & Sutter, 2007).…”
Section: Subjects and Treatmentsmentioning
confidence: 99%
“…Previous work highlights that group-based approaches are more appropriate when dealing with unfamiliar and complex questions given that a group setting facilitates information sharing and deliberation (Robinson et al, 2008;Lienhoop & Fischer, 2009). Further, collective decision making is of great interest when it comes to participatory planning, given that relevant decisions will be made in the context of small unitary groups (Kocher & Sutter, 2007).…”
Section: Subjects and Treatmentsmentioning
confidence: 99%
“…A few examples (e.g. Robinson et al, 2008) have shown that the environmental values of stakeholders can be changed as a result of learning through deliberation, however, there is much more to be learnt about knowledge exchange and the ways in which different knowledge systems are prioritised. To this end, critical reflection on the use of a deliberative approach will yield important information about its virtues and limitations.…”
Section: Participatory Assessments Of System History and Future Scenamentioning
confidence: 99%
“…The opportunity for knowledge exchange and learning, in particular, can change the values of stakeholders that were a result of incomplete or misinformation. Robinson et al (2008) reflected on their experience of using deliberative citizen's juries to derive a willingness to pay (WTP) for water quality improvements in the Bremer River catchment, Queensland, Australia. They found that citizens' juries result in an improved understanding of the proposals on the part of participants when compared with those asked to provide a WTP as individuals, and through statistical analysis they discovered that educational background ceased to be an important determinant of WTP for jury members (Robinson et al 2008).…”
Section: Requirement Ii: To Focus On Slow Variablesmentioning
confidence: 99%
“…Robinson et al (2008) reflected on their experience of using deliberative citizen's juries to derive a willingness to pay (WTP) for water quality improvements in the Bremer River catchment, Queensland, Australia. They found that citizens' juries result in an improved understanding of the proposals on the part of participants when compared with those asked to provide a WTP as individuals, and through statistical analysis they discovered that educational background ceased to be an important determinant of WTP for jury members (Robinson et al 2008). Liu et al (2010) apply an integrated Deliberative Multi-Criteria Evaluation approach to planning the management of invasive species.…”
Section: Requirement Ii: To Focus On Slow Variablesmentioning
confidence: 99%